An Analytical Study of Islamic Teaching and its impact on Reformation and Rehabilitation of Prisoners - Alomar, Mohammed Rashed; Khan, Muhammad Hayat (Journal of Islamic and Religious Studies, 2020)
Punishment is one of the legal penalties in Islam aimed at deterrence, restraint, and reform for which reform programs, especially religious education for prisoners is necessary. This scenario raises questions about prisoner's education inside the prison and the educational structure for them. In this article, the inductive method of research is adopted. Rulings on the prison, its goals, the rule of education in prison in general, and the value of religious education, are discussed in the light of the provisions of the Qur’ān, annotations to the Ḥadīth, and the books of jurisprudence. The study concludes that the Shari’ah encouraged religious education in prisons to reform and refine prisoners, to make them well informed of the rights of other people and repent them of their bad opinion. Moreover, it facilitates them to integrate quickly into society after they leave prison. The article purposes, to achieve this beneficial education, a program consisting of a set of religious decisions. The most important of them is the study of religious beliefs and morals for prisoners, for their and society's benefit.